Analisis Determinan Yang Berhubungan Dengan Kinerja Pegawai Di Puskesmas Motui Kabupaten Konawe Utara - Agnes Mersatika Hartoyo (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
The performance of nurses at the Community Health Center is greatly influenced by various factors, both internal and external. Several determinants that are thought to influence nurse performance include education, knowledge, length of service, and training. Objective: To determine the factors related to nurse performance at Motui Community Health Center. Methods: This research is analytical, using a cross-sectional study design. The population in this study were all employees working at the Motui Community Health Center, namely 50 people with ANS status. The sample of this study was 42 people selected using a purposive sampling technique. Data were collected using a questionnaire that measured education, knowledge, length of service, training, and nurse performance. Data analysis was performed using the chi-square test with the help of SPSS version 25.0. Results: The results showed that there was a significant relationship between education (x count = 6.19), knowledge (x count = 5.768), length of service (x count = 7.527), and training (x count = 15.881). Conclusion: Education, knowledge, length of service and training are determinants that influence employee performance at Motui Health Center. Therefore, improving the knowledge and training of nurses can improve their performance quality. Policies are needed to support the improvement of nurse competence through continuing education.